PENGARUH MODEL PEMBELAJARAN KOOPERATIF PICTURE DENGAN MEDIA ALPHABET CARD TERHADAP KEMAMPUAN MEMBACA SISWA SEKOLAH DASAR - Aan Andriani; Decenni Amelia (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
The low reading ability of students is caused by various factors, one of which is the lack of interest in reading among students. The aim of this research is to measure the initial reading ability of elementary school students, especially grade I students. This type of research is quantitative research, using experimental methods. The sampling technique was carried out using a purposive sampling technique. In obtaining data, researchers carried out an initial test (pretest) and a final test (posttest). The data technique used is descriptive analysis techniques and descriptive statistical analysis by testing hypotheses using t-test statistics. The data obtained was then analyzed using statistical analysis techniques, namely descriptive statistics. Based on the hypothesis test, it can be concluded that the picture and picture cooperative learning model assisted by alphabet card media affects the reading ability of elementary school students.